2022
DOI: 10.1021/acsanm.2c01904
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Au Nanoparticle Monolayers on Silicon in Two- and Three-Dimensions for Surface-Enhanced Raman Scattering Sensing

Abstract: Gold nanoparticle/silicon composites are canonical substrates for sensing applications because of their geometry-dependent physicochemical properties and high sensing activity via surface-enhanced Raman spectroscopy (SERS). The self-assembly of gold nanoparticles (AuNPs) synthesized via wet-chemistry on functionalized flat silicon (Si) and vertically aligned Si nanowire (VA-SiNW) arrays is a simple and cost-effective approach to prepare such substrates. Herein, we report on the critical parameters that influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 75 publications
5
31
0
Order By: Relevance
“…NanoSi-CDs were obtained by continuous mixing of NanoSi and CDs under magnetic stirring (Figure a). Because of the capillary force as previously reported, the as-prepared NanoSi-CDs showed good dispersion (Figure e) with a size of ∼350 nm (Figure e and Table S1), which is the same as NanoSi. Differently, CDs were found in the gaps of the hairy material (Figure f) and the lattices of CDs were about 0.21 nm (inset of Figure f), which suggested that CDs were successfully loaded into NanoSi.…”
Section: Resultssupporting
confidence: 76%
“…NanoSi-CDs were obtained by continuous mixing of NanoSi and CDs under magnetic stirring (Figure a). Because of the capillary force as previously reported, the as-prepared NanoSi-CDs showed good dispersion (Figure e) with a size of ∼350 nm (Figure e and Table S1), which is the same as NanoSi. Differently, CDs were found in the gaps of the hairy material (Figure f) and the lattices of CDs were about 0.21 nm (inset of Figure f), which suggested that CDs were successfully loaded into NanoSi.…”
Section: Resultssupporting
confidence: 76%
“…While every single measurement on the AuRh_Au NR dimers shows two strong peaks which can be attributed to aromatic ring vibrations of 4-MBA at 1584 cm −1 and at 1073 cm −1 , 65,66 these peaks were not observed in any of the Raman spectra measured on the AuRhAu NRs and the other reference samples (Fig. S10, ESI†).…”
Section: Resultsmentioning
confidence: 98%
“…Attractive interactions among each AuNP dimer might encourage aggregation. Bartschmid et al have observed similar cluster formation of AuNPs on silicon substrates . Compared to pure DNA origami, the presence of gold nanoparticles impairs the adsorption behavior of AuNP dimers.…”
Section: Resultsmentioning
confidence: 99%
“…Bartschmid et al have observed similar cluster formation of AuNPs on silicon substrates. 44 Compared to pure DNA origami, the presence of gold nanoparticles impairs the adsorption behavior of AuNP dimers. Nonetheless, PSA clearly demonstrates the ability to isolate single nanostructures for single-molecule experiments.…”
Section: The Influence Of Nanostructure Concentration and Incubation ...mentioning
confidence: 99%